Responding to Riots A Comparative Study of Elite Responses to Cronulla 2005 and England 2011 - Thirunavukkarasu, Hariharan (2012)
In recent summers, rioting around Cronulla and throughout England has sparked debates about their causes. While there has been a concerted effort to analyse these, there has been less attention on the response of political elites. Ultimately, the response of political elites determines if public policy is used to address the causes of the rioting. This study seeks to remedy this omission by conducting a comparative study of the response of political elites and the media to the Cronulla Riots of 2005 and English Riots of 2011. It contends that political elites in Australia responded to the riots by framing the riots largely as a law and order problem. In contrast, British political elites offered a greater variety of explanations in their analysis of their rioting. Similarly, media outlets in both nations explored a variety of causes for the riots, including race, class, poverty and a culture of criminality. This study claims that the anomalous response of Australian political elites elucidates certain idiosyncrasies of Australia’s political culture, including its reluctance to discuss race, and tendency to respond to complex issues through a law and order framework